DETERMINAN FISCAL STRESS DI KOTA LANGSA - Fevi Prastika Dewi; Tuti Meutia; Afrah Junita (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This research aims to determine the influence of the variables Growth in Original Regional Income, Economic Growth and Capital Expenditures on Fiscal Stress in Langsa City, either partially or simultaneously. The data used is Regional Original Income and Capital Expenditure data from 2008-2017 obtained from the Langsa City Regional Financial Management Agency (BPKD), as well as Gross Regional Domestic Product (GRDP) data for 2008-2017 obtained from the Langsa City Central Statistics Agency website. The data analysis methods used are the Classic Assumption Test, multiple linear regression analysis, and the coefficient of determination test. The results of the research show that partially the growth variables of local original income and capital expenditure have an effect on fiscal stress in Langsa City, while the economic growth variable has no effect on fiscal stress in Langsa City. Simultaneously, the variables of local original income growth, economic growth and capital expenditure influence fiscal stress in Langsa City